Characterization and long-term follow-up of children with brugada syndrome: experience from a tertiary paediatric referral centre. (3rd October 2022) - Fernandes, S; Saleiro, C; Palma, A; Faim, D; Dias, J; Borges, I; Santos, I; Andrade, H; Martins, H; Pires, A
Abstract: Introduction: Brugada syndrome (BrS) is an autosomal dominant channelopathy, which typically presents in young adults. It can also be diagnosed in children, but data in this age group is scarce. Purpose: To describe the clinical features, management and long-term follow-up of children with BrS history followed-up in a tertiary paediatric referral centre. Methods: Single centre retrospective study of consecutive patients with history of BrS, defined as having a BrS positive phenotype (BrS(+)), or a negative phenotype-positive genotype (BrS(−)). They were all followed up in a paediatric heart rhythm clinic. Clinical and demographical data were collected and analysed according to the phenotype. Results: 30 patients were included, with a median age at diagnosis of 7 years (IQR 1–13) and a mean follow-up time of 7±3 years. Sixteen patients were BrS(+), predominantly male (n=13, 81%). 88% (n=14) performed a genetic test, which was positive in 57% (n=8); the most frequent mutation was SCN5A (n=5). Family history of BrS was present in 56% (n=9) and almost one third had family history of sudden cardiac death (SCD). Most of the patients had a type 1 Brugada ECG pattern (n=14) and 2 patients presented a fever and drug induced pattern, respectively. Fourteen patients were BrS(−), mostly female (n=11, 79%) with a loss-of-function mutation in the SCN5A gene (n=10). They all had family members with BrS, mainly from the paternal side, and 43% (n=6) mentioned SCD history. Although most of the patients were asymptomatic, the prevalence of rhythm or conduction disturbances was not infrequent, particularly in BrS(+) patients (n=12, 75%). Also, in this group and during follow-up, 3 patients had documented supraventricular tachyarrhythmias, and 2 patients had syncope episodes, one of which required an implantable cardioverter-defibrillator. No events were reported in the BrS(−) patients. Nine patients (n=9/30, 30%) were hospitalized, 3 due to an arrhythmic event (all in the BrS(+) group). Overall, no sudden cardiac death event was reported during follow-up. Conclusion: In our study, although the majority of the patients were asymptomatic, the occurrence of arrhythmic events was not negligible, especially in the BrS(+) patients. Despite the significant family history, patients with BrS(−) had no events reported during follow-up. Nevertheless, the management of these patients is not clear cut, and a personalized therapeutic strategy with close follow-up is essential. Funding Acknowledgement: Type of funding sources: None.